Formulation, Evaluation & Optimization of Mouth Dissolving - sharma, shailesh (International Journal of Pharmaceutical & Biological Archive, 2010)
Co-processing is defined as combining two or more established excipients by an appropriate process. Co-processing excipients could lead to formation of excipients with superior properties compared with the simple physical mixture component. Co-processed particles of Ac-di-Sol and Crospovidone were prepared using a solvent i.e. Isopropyl Alcohol, which were used as a direct compressible excipients in mouth dissolving tablet formulation. The two super disintegrates were mixed in varied proportion (according to 32 factorial design) by constant stirring until all the solvent was evaporated. The semi dried mixture of super disintegrates was passed through mesh screen size no. 60 and dried in tray dryer at 60°C. A two factor three level (32) factorial design is being used to optimize the formulation. Nine such different proportionate mixtures of superdisintegrants were prepared accordingly. The concentration of processed Superdisintegrants was then optimized for DT 35 secs. and friability 0.5% and used to formulate mouth dissolving tablet by direct compression method using other commonly used excipients and evaluated for disintegration time, wetting time, tablet hardness and percent friability. A decrease in disintegration time and wetting time was noted with tablet prepared by processed superdisintegrants when compared with tablet formulated using Ac-di-sol, Crospovidone alone; however there was no significant change in tablet hardness and percent friability.